Determination Analysis of Implementation of Good Governance Understanding and Audit Independence on Auditor Performance in Public Accounting Offices - W A Astuti; I S Agiva (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to examine and analyze the auditor’s perception of the determination of the implementation of the understanding of good governance and auditor independence in auditor performance. The data collection method used is descriptive quantitative method which is a research method that utilizes quantitative data and is described descriptively by distributing questionnaires. The respondents of this research are auditors who work at the Public Accounting Firm (KAP) in Bandung, West Java. The sampling method used is purposive sampling with a sampling technique with certain considerations. And hypothesis testing is done with Statistical Product and Service Solutions (SPSS) software. The study prove that the Implementation of Good Governance Understanding with Auditor Performance at KAP in Bandung is quite good, this is because auditors try to carry out their profession by obeying generally accepted accounting principles and guided by SPAP. While the Independence of Auditors in Auditor Performance at KAP in Bandung is also quite good, this is because the auditors try to maintain the independence of a high auditor, then other parties will find it difficult to influence or control the auditor where the auditor will always consider the various facts found in the auditor. conduct audits, and also in formulating and in expressing opinions and thus will have an impact on the level of achievement of the auditors which will be better in other languages, namely to produce better performance.